2021
DOI: 10.3390/cancers13071576
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Alleviate Peripheral Neuropathy Induced by Anticancer Drugs

Abstract: Purpose: This study aimed to assess the potential of flavonoids in combating CIPN. Methods: PubMed and Google Scholar were used, and studies that investigated flavonoids in models of CIPN and models of neuropathic pain similar to CIPN were included. Only studies investigating peripheral mechanisms of CIPN were used. Results: Flavonoids inhibit several essential mechanisms of CIPN, such as proinflammatory cytokine release, astrocyte and microglial activation, oxidative stress, neuronal damage and apoptosis, mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…[35,36] Based on this theory, numerous chemicals and nutraceuticals with antioxidant activity have been examined in vivo studies and clinical trials to evaluate their efficiency toward peripheral neurotoxicity triggered by chemotherapeutics. [37][38][39][40] Neurodegeneration resulted from oxidative damage could occur due to bio-energetic failure, biomolecular damage, or weakening of antioxidant defence mechanisms. [41] Considering the ameliorative effects of several antioxidant molecules against chemotherapeutics-induced peripheral neuropathy, NRG was tested in the current study as a potent antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…[35,36] Based on this theory, numerous chemicals and nutraceuticals with antioxidant activity have been examined in vivo studies and clinical trials to evaluate their efficiency toward peripheral neurotoxicity triggered by chemotherapeutics. [37][38][39][40] Neurodegeneration resulted from oxidative damage could occur due to bio-energetic failure, biomolecular damage, or weakening of antioxidant defence mechanisms. [41] Considering the ameliorative effects of several antioxidant molecules against chemotherapeutics-induced peripheral neuropathy, NRG was tested in the current study as a potent antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…The glands became less in number and lining epithelium became flattened in the standard drug-treated group. Hyperplasia of prostatic epithelial cells and stromal cells occurs, which subsequently results in lower urinary tract symptoms ( Jin et al, 2021 , Zhang et al, 2021 , Siddiqui et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there was currently no effective treatment to control oxaliplatin-induced NP optimally. Previous reports indicated that flavonoids could prevent the occurrence and development of chemotherapy-induced NP via suppressing apoptosis, oxidative stress, astrocyte and microglial activation, and inflammatory responses (Zhang Singh et al 2020;Xie et al 2020;Siddiqui et al 2021). Therefore, flavonoids may be a novel analgesic drug in the prevention and treatment of chemotherapy-induced NP.…”
Section: Discussionmentioning
confidence: 99%